Sistemas individuais alternativos de tratamento de esgoto sanitário - Carneiro, Mariko de Almeida (2018)
WHO (2017b) estimates that 4.5 billion people in the world do not have access to safe sanitation services. The context is not very different in Brazil, where despite significant advances in the sanitation sector, only, 51,9% of the Brazilian population has access to sewage service and 44,9% of the sewage generated in the country suffer some type of treatment (SNIS, 2018). In order to increase sanitation service access it is necessary to provide sewage treatment systems, such as decentralised (single) systems: technologies applied in places with difficult access to the sewage network or in situation that increases the costs to implement or maintain the system. In this context, the present work evaluated the performance of two alternative systems of raw sewage treatment: a vertical flow constructed wetland (French compact system) and a sequencing batch reactor (SBR), comparing the efficiency of pollutants removal with conventional single systems. During 12 months of monitoring, the French compact system removed 87,8% of COD and 74,3% of BOD, while the SBR removed 94,5% of COD and 86,6% of BOD. The alternative decentralised systems showed superior performance to conventional systems such as septic tank followed by anaerobic filter. Therefore, the single alternative systems studied were feasible solutions for the treatment of sanitary sewage of housing unit and small communities.